Pharmacological insights into Ipomoea staphylina: Therapeutic activities and the isolated bioactive metabolic compounds - Narayanan, Lakshmanan; SR, Suseem (Mongolian Journal of Chemistry, 2024)
This review comprehensively explores I. staphylina's traditional uses, diverse applications, and pharmacological activities. Extensively used in traditional medicine, this plant addresses a range of ailments, including stomach disorders, respiratory issues, and rheumatism. Research has highlighted its significant antimicrobial, anti-inflammatory, antioxidant, antidiabetic, anthelmintic, and analgesic properties. Notably, its antiulcer activity highlights its potential as a novel antiulcer agent, while hepatoprotective and nephroprotective effects suggest therapeutic applications in liver and kidney disorders. Studies on its anti-diabetic potential show significant reductions in blood glucose levels and positive impacts on biochemical markers. The plant's anti-mutagenic activity against base-pair mutations expands its potential applications. The review also discusses the isolation and pharmacological applications of pure compounds identified through LC-MS and NMR analyses. This review identifies I. staphylina as a promising source of bioactive compounds with therapeutic potential, emphasizing the need for further research to isolate and characterize its active constituents.